Therapy options for malignant eyelid tumors - Weiling, Max; Bergua, A.; Kruse, Friedrich; Holbach, L. (Ophthalmologe, 2016)
Basal cell carcinomas are the most common malignant tumors of the eyelids. Patient history, clinical symptoms and signs, inspection, palpation and slit-lamp examination usually allow a working diagnosis; however, the clinical diagnosis requires histopathological confirmation and determination of the histopathological type. Squamous cell carcinomas, sebaceous gland carcinomas, melanomas and Merkel cell carcinomas can metastasize usually via the lymph vessels into the regional lymph nodes. Microscopically controlled excision of the primary tumor into healthy tissue is most commonly the first goal. Palpation and ultrasonography of the regional lymph nodes and also computed tomography (CT) with contrast enhancement and magnetic resonance imaging (MRI) for tumors with perineural sheath cell invasion are necessary to define the TNM stage. Non-surgical treatment options are becoming more popular in the further management of malignant eyelid tumors.
EVALuna2:21311